Structural Correlates of Neurological Signs in Huntington’s Disease: A Quantitative Approach - E. A. Loh; J. K. A. Roberts; E. Mohr (Behavioural Neurology)
Huntington's disease (HD) is a genetically transmitted disorder associated with atrophy of the basal ganglia. Studies of the neuroanatomical correlates of HD have focused primarily on the anterior areas of the basal ganglia and on establishing an association between structural changes resulting from the presence and course of the illness. The objective of the present study was to assess the value of measurements of the third ventrical and lentiform regions. Computed tomographic (CT) brain scan measures of the basal ganglia of patients in the “early” and “late” stages of the disease were correlated with scores on a quantified neurological examination (QNE) and compared with scans of age-matched control groups. Basal ganglia atrophy was assessed by two conventional “anterior” measures: the maximal distance between the frontal horns of the lateral ventricles (FH) and the minimum distance between the caudate nuclei (CC), and two measures of more “posterior” regions: the width of the third ventricle (3V), and a measure of the lentiform regions (LENTI). In the group of patients with HD, CT scan measures were strongly correlated with disease duration. Further, in the “late” group, all CT measures were significantly correlated with QNE scores, with the two “posterior” measures being equally, if not more strongly correlated with QNE scores than the conventional “anterior” measures. Separate correlations of the CT indices of atrophy and QNE scores in the “early” and “late” HD groups revealed relationships between basal ganglia atrophy and motor abnormality consistent with earlier reports.